The Contribution of Environmental CSR Communication in Overcoming Ecological Crises in the Coastal Region - Widiada, I Gede; Budiartini, Ni Nengah; Sutama, I Wayan (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relations, 2025)
Coastal regions are increasingly susceptible to an intensifying ecological crisis driven by climate change and anthropogenic activities, necessitating an integrated and participatory approach to environmental governance. This study seeks to elucidate the role of transparent, dialogical, and culturally resonant corporate social responsibility (CSR) practices, such as local recruitment, procurement, and support for community initiatives, in fostering participatory engagement and facilitating collective ecological action. The findings indicate that dialogical communication strategies, including collaborative forums, inclusive storytelling, and regular feedback mechanisms, effectively mobilize diverse stakeholders and integrate ecological interventions within local values and practices. Employing a case study methodology, this research highlights the capacity of CSR practices to enhance the legitimacy, impact, and sustainability of environmental initiatives, thereby increasing their resilience to challenges and likelihood of long-term sustainability. Data collection involved interviews and observations of a purposively selected cohort of individuals and hotel employees. The study identifies critical contextual factors, such as cultural appropriateness, governance dynamics, and pre-existing public relations, that may limit the positive effects of CSR communication. It is imperative to address barriers such as language gaps and institutional mistrust to prevent exclusion and skepticism. These findings contribute to theoretical understanding by positioning CSR communications as integral to environmental governance, while also providing practical guidance for businesses and policymakers: prioritizing participatory and context-sensitive communication and ensuring alignment between CSR messages and substantive actions. This research underscores the strategic value of environmental CSR communication in addressing the ecological crisis through adaptive stakeholder collaboration